Nano-sized crystalline drug production by milling technology - Kunikazu Moribe (2018)
Nano-formulation of poorly water-soluble drugs has been developed to enhance drug dissolution. In this review, we introduce nano-milling technology described in recently published papers. Factors affecting the size of drug crystals are compared based on the preparation methods and drug and excipient types. A top-down approach using the comminution process is a method conventionally used to prepare crystalline drug nanoparticles. Wet milling using media is well studied and several wet-milled drug formulations are now on the market. Several trials on drug nanosuspension preparation using different apparatuses, materials, and conditions have been reported. Wet milling using a high-pressure homogenizer is another alternative to preparing production-scale drug nanosuspensions. Dry milling is a simple method of preparing a solid-state drug nano-formulation. The effect of size on the dissolution of a drug from nanoparticles is an area of fundamental research, but it is sometimes incorrectly evaluated. Here, we discuss evaluation procedures and the associated problems. Lastly, the importance of quality control, process optimization, and physicochemical characterization are briefly discussed. © 2013 Bentham Science Publishers.